ELT LEARNING MEDIA FOR YOUNG LEARNERS: FAMILY-THEMED PICTURE STORIES - Anselmus Inharjanto; Lisnani Lisnani (University of Kuningan, 2021)
The study aims at investigating whether the family-themed picture stories for young learners were valid as learning media for English Language Teaching (ELT). The researchers developed three picture stories related to family as prototypes. The research procedure was proposed by Akker, which comprised analysis, design, evaluation, and revision. The validity was reviewed by the experts of content, instructional design and media or product design. The mean of content validity of three prototypes is 4.26 which is at very highly valid level. In term of construct validity, the average score of construct validity of three stories is 4.23 which is at very highly valid level. The average score of media or product design validity of the prototypes is 4.36 which is at very highly valid level. Thus, the study result shows that, overall validities of content, construct, and media or product design of the three picture stories are 4.28, which is at very highly valid level. In conclusion, the set of family-themed picture stories as learning media are valid and categorized as very highly valid level; consequently, they are likely to facilitate Teaching English to Young Learners (TEYL).Keywords: learning media; TEYL; picture stories